Penatalaksanaan Apeksifikasi: Pada Fraktur Gigi Depan Atas Karena Trauma - Dwi Warna Aju Fatmawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Apexification is a procedure well recognized and accepted by clinicians and researchers alike. Apexification is an endodontic treatment that intends to stimulate of apex formation. One material in dentistry is calcium hydroxide that is most commonly used to induce an apical hard tissue barrier. Because of the capacity to promote environmental condition for tissue repair, calcium hydroxide can be used in the management of most endodontic problems, such as pulp capping, pulpotomy, root canal treatment, apexification and various endodontic situations. Due to its high alkalinity is has an antibacterial effect, promotes mineralization, induces healing, and initiates hard tissue formation. Although there have been many reports on the subject, the mechanisms of action are still unknown.